2006
DOI: 10.1128/aac.00381-05
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlation of the CLSI Susceptibility Breakpoint for Piperacillin- Tazobactam against Extended-Spectrum-β-Lactamase-Producing Escherichia coli and Klebsiella Species

Abstract: We assessed infections caused by extended-spectrum-␤-lactamase-producing Escherichia coli or Klebsiella spp. treated with piperacillin-tazobactam to determine if the susceptibility breakpoint predicts outcome. Treatment was successful in 10 of 11 nonurinary infections from susceptible strains and in 2 of 6 infections with MICs of >16/4 g/ml. All six urinary infections responded to treatment regardless of susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 27 publications
1
34
1
2
Order By: Relevance
“…Among the K. pneumoniae isolates studied, the piperacillin-tazobactam regimen produced the most profound reduction in CFU (0.75 and Ͼ1-log-unit decreases) over the 24-h treatment period. The efficacy of piperacillin-tazobactam against ESBL-positive organisms has been demonstrated in several studies, with some studies showing that piperacillin-tazobactam was the most active agent studied (9,14,18). In these, efficacy was dependent not only on the actual MIC of the organism, but also on the % fT Ͼ MIC achieved by the piperacillin-tazobactam regimen, striving for a % fT Ͼ MIC of Ͼ30 to 35% (1,9).…”
Section: Discussionmentioning
confidence: 99%
“…Among the K. pneumoniae isolates studied, the piperacillin-tazobactam regimen produced the most profound reduction in CFU (0.75 and Ͼ1-log-unit decreases) over the 24-h treatment period. The efficacy of piperacillin-tazobactam against ESBL-positive organisms has been demonstrated in several studies, with some studies showing that piperacillin-tazobactam was the most active agent studied (9,14,18). In these, efficacy was dependent not only on the actual MIC of the organism, but also on the % fT Ͼ MIC achieved by the piperacillin-tazobactam regimen, striving for a % fT Ͼ MIC of Ͼ30 to 35% (1,9).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent retrospective studies of clinical outcomes from E. coli and K. pneumoniae ESBL-producing isolates argue for the efficacy of piperacillin-tazobactam in the treatment of these infections (135,336,370,420). Gavin et al showed that when in vitro testing revealed susceptibility to piperacillin-tazobactam (Յ16/4 g/ml), successful outcomes were seen in 10 out of 11 non-urinary tract infections (135).…”
Section: ␤-Lactamase Inhibitors In Clinical Practicementioning
confidence: 99%
“…Gavin et al showed that when in vitro testing revealed susceptibility to piperacillin-tazobactam (Յ16/4 g/ml), successful outcomes were seen in 10 out of 11 non-urinary tract infections (135). An examination of 43 bloodstream infections caused primarily by CTX-M ESBL-producing E. coli isolates revealed that piperacillin-tazobactam, amoxicillin-clavulanate (i.v.…”
Section: ␤-Lactamase Inhibitors In Clinical Practicementioning
confidence: 99%
“…Clinicians must keep in mind that presence of a chromosomal AmpC enzymes that is normally resistant to inactivation by a beta-lactamase inhibitor may be present [70]. Based on this and the data obtained from microbiological and clinical observations, we do not regard beta-lactam/beta-lactamases inhibitor combinations as a suitable option for serious infections due to ESBL-producing enterobacteria [87,88].…”
Section: Beta-lactam/beta-lactamases Inhibitor Combinationsmentioning
confidence: 99%